Unravelling a mechanistic link between mitophagy defect, mitochondrial malfunction, and apoptotic neurodegeneration in Mucopolysaccharidosis VII - Nishan Mandal; Apurba Das; Rupak Datta (Neurobiology of Disease, 2025)
Cognitive disability and neurodegeneration are prominent symptoms of Mucopolysaccharidosis VII (MPS VII), a lysosomal storage disorder caused by β-glucuronidase enzyme deficiency. Yet, the mechanism of neurodegeneration in MPS VII remains unclear thereby limiting the scope of targeted therapy. We aimed to bridge this knowledge gap by employing the β-glucuronidase-deficient (CG2135−/−) Drosophila model of MPS VII. Taking cues from our initial observation that the adult CG2135−/− flies displayed enhanced susceptibility to starvation, we investigated potential impairments in the autophagy-lysosomal clearance machinery in their brain to dissect the underlying cause of neurodegeneration. We found that both autophagosome biogenesis and lysosome-mediated autophagosomal turnover were impaired in the CG2135−/− fly brain. This was evidenced by lower Atg8a-II levels, reduced Atg1 and Ref(2)P expression along with accumulation of lipofuscin-like inclusions and multilamellar bodies. Mitophagy was also found to be defective in their brain, resulting in buildup of enlarged mitochondria with distorted cristae and reduced membrane potential. This, in turn, compromised mitochondrial function, as reflected by drastically reduced brain ATP levels. Energy depletion triggered apoptosis in neuronal as well as non-neuronal cells of the CG2135−/− fly brain, where apoptotic dopaminergic neurons were also detected. Interestingly, resveratrol treatment corrected the mitophagy defect and prevented ATP depletion in the CG2135−/− fly brain, providing an explanation for its neuroprotective effects. Collectively, our study reveals a pharmacologically targetable mechanistic link between mitophagy defect, mitochondrial malfunction, and apoptotic neurodegeneration in MPS VII.